Usability of Emergency Department Information System Based on Users' Viewpoint; a Cross-Sectional Study - Almasi, Sohrab; Mehrabi, Nahid; Asadi , Farkhondeh; Afzali , Mahboobeh (Archives of Academic Emergency Medicine, 2022)
Introduction: The emergency department is of special importance due to its emergency and vital services, the high volume of referrals, and the patients' physical condition. Thus, it requires a well-designed information system with no usability problems. This study aimed to evaluate the usability of the emergency department information system from users' perspectives. Methods: This was a cross-sectional study. The research setting was the emergency department of 3 hospitals. The research instrument was a 37-item questionnaire adapted from the USE and ISO Metrics questionnaires, consisting of five dimensions measuring the usefulness of the system, ease of use, ease of learning, user satisfaction, and suitability for the task. The content validity of the questionnaire was examined using the content validity ratio and content validity index, and its reliability was assessed using Cronbach's alpha (α = 0.88). Results: Fifty questionnaires were administered in the three hospitals, and the response rate was 80%. According to the findings, 55% of the respondents were female. The highest mean scores belonged to usefulness in emergency department information system (EDIS) A, ease of use in EDIS B, ease of learning in EDIS A, user satisfaction in EDIS C, and suitability for the task in EDIS A. According to the usability evaluation criteria, ease of learning (3.66 ± 0.74), usefulness (3.53 ± 0.87), and suitability for the task (3.47 ± 0.96) received the highest scores, and the lowest scores belonged to user satisfaction (3.29 ± 1.01) and ease of use (3.12 ± 1.00). Conclusion: In terms of usability criteria, the emergency department information system is at a relatively good level. The usability of these systems can be further enhanced by considering the users' working needs, improving software flexibility, customizing the software, using data visualization tools, observing consistency of features and standards, and increasing the quality of information and system services.